RNA expression and disease tolerance are associated with a “keystone mutation” in the ochre sea star Pisaster ochraceus - Chandler, V. Katelyn (PeerJ, 2017)
An overdominant mutation in an intron of the elongation factor 1-α (EF1A) gene in the sea star Pisaster ochraceus has shown itself to mediate tolerance to “sea star wasting disease”, a pandemic that has significantly reduced sea star populations on the Pacific coast of North America. Here we use RNA sequencing of healthy individuals to identify differences in constitutive expression of gene regions that may help explain this tolerance phenotype. Our results show that individuals carrying this mutation have lower expression at a large contingent of gene regions. Individuals without this mutation also appear to have a greater cellular response to temperature stress, which has been implicated in the outbreak of sea star wasting disease. Given the ecological significance of P. ochraceus, these results may be useful in predicting the evolutionary and demographic future for Pacific intertidal communities.